2013
DOI: 10.1089/ars.2012.4687
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Ras and Rho GTPases: Mechanism and Function

Abstract: Significance: Oxidation and reduction events are critical to physiological and pathological processes and are highly regulated. Herein, we present evidence for the role of Ras and Rho GTPases in controlling these events and the unique underlying mechanisms. Evidence for redox regulation of Ras GTPases that contain a redox-sensitive cysteine (X) in the conserved NKXD motif is presented, and a growing consensus supports regulation by a thiyl radical-mediated oxidation mechanism. We also discuss the debate within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 58 publications
(88 reference statements)
0
76
0
Order By: Relevance
“…The malignant redox environment is closely interwoven with many oncogenes including RAS, to allow for tumor progression and metastasis (6,36,37). However, it is known that this crosstalk leads to an increase of cellular ROS production via overactivation of NADPH oxidases among others (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…The malignant redox environment is closely interwoven with many oncogenes including RAS, to allow for tumor progression and metastasis (6,36,37). However, it is known that this crosstalk leads to an increase of cellular ROS production via overactivation of NADPH oxidases among others (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, impaired cell migration after PDI silencing closely correlated with decreases in Rac1 or RhoA activity and profound disruption of cytoskeletal structures, such as stress fibers, focal adhesions, and adhesion vesicles. Importantly, Rac1 and RhoA can be strongly regulated by redox mechanisms, although it is yet unclear to what extent this occurs in vivo (118). Overall, these emerging findings allow the proposal that PDI may act as novel redox-related organizer of the NADPH oxidase complex.…”
Section: Pdi Interaction With Nox Nadph Oxidasementioning
confidence: 90%
“…Rho family GTPases containing this redox-sensitive motif include RhoA, RhoB, RhoC, RhoG, all Rac isoforms, and Cdc42 (for sequence comparison of the redox-sensitive motifs in Ras and Rho family GTPases, see ref. 6). The seminal papers that first identified the redox-sensitive properties of this motif in the canonical Rho family members (RhoA, Rac1, and Cdc42) showed that exposure to free radical oxidants (nitrogen dioxide and superoxide) resulted in increased nucleotide dissociation, similar to that observed for Ras.…”
Section: Redox Regulation Of Racmentioning
confidence: 99%